Congruence between perceived and theoretical knowledge before and after an internet-based continuing education program about VLU nursing care - Ylönen M.; Viljamaa J.; Isoaho H.; Junttila K.; Leino-Kilpi H.; Suhonen R. (United Kingdom, 2022)
Background: Previous research has revealed nurses' knowledge gaps in venous leg ulcer (VLU) nursing care, and continuing education is needed. The closer nurses' perceived knowledge is to their evidence-based theoretical knowledge, the better possibilities they have to conduct evidence-based VLU nursing care.
Objectives: To assess the congruence between nurses' perceived and theoretical knowledge about VLU nursing care before and after an internet-based education about VLU nursing care (eVLU).
Design: Quasi-experimental study with intervention and comparison groups and pre- and post-measurements.
Setting: Home health care in two Finnish municipalities.
Participants: Nurses (n = 946) working in home health care were invited to participate. In the intervention group, 239 nurses and 229 nurses in the comparison group met the inclusion criteria, and they were all recruited to the study.
Method: Nurses were divided into intervention and comparison groups with lottery between the municipalities. Nurses in both groups took care of patients with VLU according to their organizations' instructions. In addition to this, nurses in the intervention group received a 6-week eVLU while those in the comparison group did not. Data were collected with a questionnaire about perceived and theoretical knowledge before education, at six weeks, and at 10 weeks. The percentages of congruence were calculated at every measurement point, and the McNemar test was used to detect statistical significance of changes between measurements.
Results: The increase of congruence was more often statistically significant in the intervention group than in the comparison group.
Conclusion: The results support the hypothesis that the congruence between perceived and theoretical knowledge will be higher among nurses receiving eVLU. Because of the low participation and drop-outs, the results should be interpreted with caution.